2013
DOI: 10.1016/j.micinf.2013.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Ehrlichia moonlighting effectors and interkingdom interactions with the mononuclear phagocyte

Abstract: Ehrlichia chaffeensis is an obligately intracellular gram negative bacterium with a small genome that thrives in mammalian mononuclear phagoctyes by exploiting eukaryotic processes. Herein, we discuss the latest findings on moonlighting tandem repeat protein effectors and their secretion mechanisms, and novel molecular interkingdom interactions that provide insight into the intracellular pathobiology of ehrlichiae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 64 publications
2
21
0
Order By: Relevance
“…To date, the molecular mechanisms by which Ehrlichia enters and modulates host cells are not well understood (4,(6)(7)(8), but our findings regarding Wnt pathways are consistent with previous reports that described some characteristics of cellular signaling upon internalization of ehrlichiae (43,44). E. chaffeensis enters the monocyte through lipid raft-caveola-mediated endocytosis, where it can reside within a cytoplasmic vacuole that resembles an early endosome, preventing lysosomal fusion and protecting it from killing (44).…”
Section: Discussionsupporting
confidence: 91%
“…To date, the molecular mechanisms by which Ehrlichia enters and modulates host cells are not well understood (4,(6)(7)(8), but our findings regarding Wnt pathways are consistent with previous reports that described some characteristics of cellular signaling upon internalization of ehrlichiae (43,44). E. chaffeensis enters the monocyte through lipid raft-caveola-mediated endocytosis, where it can reside within a cytoplasmic vacuole that resembles an early endosome, preventing lysosomal fusion and protecting it from killing (44).…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, our current study and previous publications showed virB6-4, the largest and most downstream gene in the virB6 operon (EHF_0445, APH_0377, MC1_00820) is consistently disrupted by Himar1 transposon without affecting Ehrlichia, Anaplasma, or Rickettsia growth in mammalian host cells (Felsheim et al, 2006;Lamason et al, 2018). Despite extensive arrays of in vitro functions proposed for TRP120 (former gp120) for E. chaffeensis infection of macrophages (Yu et al, 2000;Luo et al, 2011;Zhu et al, 2011;Dunphy et al, 2013Dunphy et al, , 2014, the gene encoding HF strain TRP120 homolog had the insertion near 5 ′ end, implicating this gene is dispensable for Ehrlichia HF infection of macrophages. TRP120 appears to be an abundantly produced protein in E. chaffeensis (Yu et al, 2000), TRP mutant of HF obtained in our study would help elucidate in vivo or other functions of TRP120 in the future.…”
Section: Discussionsupporting
confidence: 47%
“…lar trafficking and cytoskeletal organization, and apoptosis (4,5). Most recently, E. chaffeensis via the TRP120 effector was shown to activate Wnt and Notch signaling pathways to promote intracellular survival (6,7).…”
mentioning
confidence: 99%